APPLIED ASPECTS OF SLCO1B1 PHARMACOGENETIC TESTING FOR PREDICTING OF STATIN-INDUCED MYOPATHY AND PERSONALIZATION OF STATINS THERAPY - D. A. Sychev; G. N. Shuev; A. B. Prokofiev (Столичная издательская компания, 2015)
The clinical significance of the SLCO1B1 gene polymorphism (encoding an organic anion transport polipeptide) in the development of statin induced myopathy is considered. Possible tactics of statin dose determination on the basis of pharmacogenetic testing is discussed. Indications for the use of this approach in clinical practice that should increase the efficacy and safety of the statin therapy are also considered.